The teaching about the care of the elderly in nursing training: the situation in Portugal - Santos, Silvana Sidney Costa; Lopes, Manuel José; Gemito, Maria Laurência; Casas-Novas, Maria Vitória; Pinheiro, Felícia Tavares (Rev Rene, 2013)
This paper aims to look at the teaching situation of the nursing undergraduate degree’s courses about eldercare in Portugal. A documentary research on the teaching programs in 39 nursing schools, 26 schools presented syllabus units related to the topic ‘eldercare’ and in eight of these schools the contents of the units were identified. Using textual analysis and from the categories we concluded that the teaching regarding eldercare for the nurse training in Portugal is focused on hospital care; it is directed to the adult/elderly/family; it explores the definitions related to the aging process; it explores community issues, legislation and research. People responsible for the design/monitoring of teaching programs should include teaching regarding eldercare in the nurse training, considering that the elder population is increasing in Portugal. DOI:https://doi.org/10.15253/2175-6783.20130004000017